2021
DOI: 10.1002/aic.17225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrodynamic heterogeneity on micromixing intensification in a Taylor–Couette flow reactor with variable configurations of inner cylinder

Abstract: Effect of hydrodynamic heterogeneity on micromixing intensification in a Taylor-Couette flow (TC) reactor with variable configurations of inner cylinder has been investigated by adoption of a parallel competing iodide-iodate reaction system. Two types of inner cylinder, circular inner cylinder and lobed inner cylinder (CTC and LTC), were used to generate hydrodynamic heterogeneity, focusing on the effects of the Reynolds number, the acid concentration, and the feeding time on the micromixing performance. Segre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…20 When the inner cylinder rotates at a certain speed, Taylor vortex flow will appear in the gap, and the impact jet area formed between the opposite rotating ring Taylor vortex enhances the mass transfer and facilitates mixing. 21 24 The excellent mixing and periodic flow of the Taylor vortex promote the formation of spherical, homogeneous agglomerated particles. Kim et al 25 investigated the effect of the Taylor vortex on the crystallization process of the gas− liquid reaction of calcium carbonate and found that the Taylor vortex enhanced the mass transfer at the gas−liquid interface, thus increasing the crystallization yield.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 When the inner cylinder rotates at a certain speed, Taylor vortex flow will appear in the gap, and the impact jet area formed between the opposite rotating ring Taylor vortex enhances the mass transfer and facilitates mixing. 21 24 The excellent mixing and periodic flow of the Taylor vortex promote the formation of spherical, homogeneous agglomerated particles. Kim et al 25 investigated the effect of the Taylor vortex on the crystallization process of the gas− liquid reaction of calcium carbonate and found that the Taylor vortex enhanced the mass transfer at the gas−liquid interface, thus increasing the crystallization yield.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The inner cylinder rotates while the outer cylinder is fixed, and the inner and outer cylinder gap is the reaction site . When the inner cylinder rotates at a certain speed, Taylor vortex flow will appear in the gap, and the impact jet area formed between the opposite rotating ring Taylor vortex enhances the mass transfer and facilitates mixing . The simple structure and flexible operation have facilitated Taylor–Couette flow reactors’ experimental and industrial development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, fluid mixing as a common and basic unit operation has been widely developed and applied in various industrial fields, including the chemical, petroleum, pharmaceutical, and food industries. , It can be distinguished into three distinct levels as macromixing, mesomixing, and micromixing based on the space/time scale of mixing. , Specifically, the micromixing occurring at the molecular scale plays an essential role in the fast chemical reaction, as polymerization reactions, catalytic reactions, , and precipitation reactions. , The micromixing performance of reactors and the inherent reaction kinetics of the reaction determine the conversion and selectivity of reactants and the quality and yield of products. , Many scholars have studied the micromixing performance of reactors including stirred reactors, , microchannel reactors, , rotating packed-bed (RPB) reactors, , rotor–stator spinning disk reactors, , impinging jet reactors, and high-shear mixers (HSM) . For example, Liu et al investigated the micromixing characteristics of the novel large-double-blade stirring reactor and indicated that the micromixing performance was improved by increasing the feeding time and feeding in the high-local energy dissipation rate regions.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Specifically, the micromixing occurring at the molecular scale plays an essential role in the fast chemical reaction, 5 as polymerization reactions, 6 catalytic reactions, 7,8 and precipitation reactions. 9,10 The micromixing performance of reactors and the inherent reaction kinetics of the reaction determine the conversion and selectivity of reactants and the quality and yield of products. 11,12 Many scholars have studied the micromixing performance of reactors including stirred reactors, 13,14 microchannel reactors, 15,16 rotating packed-bed (RPB) reactors, 17,18 rotor−stator spinning disk reactors, 19,20 impinging jet reactors, 21 and high-shear mixers (HSM).…”
Section: Introductionmentioning
confidence: 99%